BUSINESS RISK, FINANCIAL RISK AND STOCK PRICE ON THE VALUE OF CONVENTIONAL BANKING SUBSECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE (IDX) - Amanda, Silvia; Nirwana, Nihlatul Qudus Sukma (PT. Antis International Publisher, 2025)
Objective: The purpose of this study we present a case study to determine the Effect of Business Risk, Financial Risk and Stock Price on Firm Value on the Indonesia Stock Exchange. Method: This study uses a quantitative approach with a research sample of 34 companies that meet the criteria using purposive sampling technique. The analytical tool used is secondary data in the form of financial statements, data collection in the form of descriptive statistical tests and classical assumption tests. Testing with Statistical Package for the Social Sciences (SPSS). Results: The results of the hypothesis in the research that has been done show that business risk, financial risk and stock price have an influence on the value of the company. Novelty: This means that company value is able to strengthen the relationship between business risk, financial risk and stock price.